Perancangan Aplikasi Pemesanan Tiket Pariwisata Berbasis Mobile di Kota Yogyakarta - Dwiki Baskoro Pamungkas; Agus Suhendar (Universitas Islam Raden Rahmat, Malang, 2024)
The development of the tourism sector in Sleman Regency is currently experiencing growth, which can be enhanced by increasing the number of tourists. One key factor supporting the growth of the tourism industry is the availability of comprehensive tourism information. Therefore, the idea has emerged to create an Android-based application with the aim of serving as a tourism promotion tool in Sleman. This application will provide information about tourist destinations in Sleman, including estimated costs required for visits. The application will be built using a Client-Server architecture, with the database server serving as the data storage location, the mobile application as the service receiver (Client), and the Webmaster as the service provider (Server). The application will also perform calculations for the ticket costs required by tourists when visiting specific destinations. This application offers services to visitors, information about the nearest routes to the location, ticket reservations, and online payments through the application.